Fedor Il'ich Dan : A Menshevik Leader in Lenin's Russia - Dan, F. (Fedor), 1871-1947 (Book collections on Project MUSE., 2016)
Two Years of Wandering is a vivid picture of life in Soviet Russia during the civil war, through the eyes of Lenin's longstanding political rival, the leading Menshevik Fedor Dan. It is the first translation into any language of Dan's memoir, written and published in Russian in 1922. Dan had been an active revolutionary and Marxist since the 1890s, and one of the Soviet leaders in 1917, but by 1920, when this memoir begins, he and his party were leading a precarious, semi-legal existence. From then until his expulsion from Soviet Russia in 1922, Dan's life as a mobilised state employee and political oppositionist took him from Moscow to the Urals, the Russo-Polish front, Soviet congresses in Moscow and Petrograd - and to prison. Now available for the first time in English, Francis King's translation of Dan's memoir sheds new light on life in the 'war communist' siege economy in the capitals and the provinces, on the mentalities of the supporters and critics of Lenin's government, and on the political logic driving the development of the Soviet one-party system and its criminalisation of any dissent. The volume is essential reading for both academics and general readers interested in the crucial political and social shifts that took place in Soviet Russia during this period of great change.